Synthesis of Iron-Doped Zirconium Titanate as a Potential Visible-Light Responsive Photocatalyst - Rian Kurniawan; Sri Sudiono; Wega Trisunaryanti; Akhmad Syoufian (Universitas Gadjah Mada, 2019)
Synthesis and properties of iron-doped zirconium titanate (ZrTiO4) as a potential visible-light-responsive photocatalyst had been conducted. Various iron dopant concentration and calcination temperature were investigated toward the properties of Fe-doped ZrTiO4. The photocatalyst material was synthesized by sol-gel and impregnation method. Titanium tetraisopropoxide (TTIP) was used as a precursor, embedded on zirconia fine powder. A certain amount of iron (1, 3, 5, 7 and 9 wt.%) was introduced into the photocatalyst system from iron(II) sulfate heptahydrate (FeSO4·7H2O). Photocatalyst with various iron concentration calcined at 500 °C. ZrTiO4 with 5% iron additionally was calcined at 700 and 900 °C. Characterization was performed by using XRD, FT-IR, SR-UV, and SEM-EDX. The presence of iron on the surface of ZrTiO4 was proved by EDX analysis. Fe-doped ZrTiO4 with the lowest bandgap (2.83 eV) is 7% of iron content after calcination at 500 °C.